2002
DOI: 10.1002/1522-2683(200202)23:4<517::aid-elps517>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Truly hypervariable DNA fingerprints due to exceptionally high mutation rates

Abstract: The power of DNA fingerprinting is due to comparatively high mutation rates of minisatellite and microsatellite DNA sequences. Studying the mating system of a parrot species (Burrowing Parrots, Cyanoliseus patagonus) using oligonucleotide probes, we observed mutation rates that are several orders of magnitude higher than those described anywhere in the literature. Most plausibly, the respective values are based on 3-4 loci with mutation rates of up to 100%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In fact, the number of diagnostic bands was very low in this family, and some bands taken as identical by descent could actually be different given that a further re‐examination revealed that some of them could not be exactly the same band in size, and their intensity on the Southern hybridization was different. The band patterns obtained with multilocus radioactive probes can be misleading and difficult to interpret in some cases, especially when the potential fathers are relatives, the population is highly inbred or when additional bands appear in the offspring due to mutation (see for instance Lubjuhn et al . 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the number of diagnostic bands was very low in this family, and some bands taken as identical by descent could actually be different given that a further re‐examination revealed that some of them could not be exactly the same band in size, and their intensity on the Southern hybridization was different. The band patterns obtained with multilocus radioactive probes can be misleading and difficult to interpret in some cases, especially when the potential fathers are relatives, the population is highly inbred or when additional bands appear in the offspring due to mutation (see for instance Lubjuhn et al . 2002).…”
Section: Discussionmentioning
confidence: 99%
“…According to accessibility, 79 nests were closely monitored in one sector of the colony as part of an ongoing study of the breeding behaviour of the species (e.g. Lubjuhn et al 2002, Masello et al 2006a and references therein, Masello et al 2006b). Nests were inspected every five days by climbing the cliff face.…”
Section: Methodsmentioning
confidence: 99%
“…Nestlings from each brood fledged also asynchronously, with an interval of 2–3 days between nestlings (Masello and Quillfeldt 2002). Burrowing parrots have a socially and genetically monogamous breeding system with intensive biparental care (Lubjuhn et al 2002, Masello et al 2002, Masello and Quillfeldt 2003). The nestlings remain in the nest for about 60 days (Masello and Quillfeldt 2002).…”
Section: Methodsmentioning
confidence: 99%